2012
DOI: 10.1242/jcs.104018
|View full text |Cite
|
Sign up to set email alerts
|

Filamin A controls matrix metalloprotease activity and regulates cell invasion in human fibrosarcoma cells.

Abstract: SummaryFilamins are an important family of actin-binding proteins that, in addition to bundling actin filaments, link cell surface adhesion proteins, signaling receptors and channels to the actin cytoskeleton, and serve as scaffolds for an array of intracellular signaling proteins. Filamins are known to regulate the actin cytoskeleton, act as mechanosensors that modulate tissue responses to matrix density, control cell motility and inhibit activation of integrin adhesion receptors. In this study, we extend the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 70 publications
4
22
0
Order By: Relevance
“…Consistent with this finding, FLNa and FLNb suppress matrix degradation and invasion in HT1080 fibrosarcoma cells. 21 Conversely, in macrophages, FLNa stabilizes podosomes, thus enhancing matrix degradation, 19 indicating that the effect of FLNs on podosome formation and matrix degradation is cell type specific. Altogether, our data support the idea that, in immature DCs, ASB2a acts as a positive regulator of ECM invasion through degradation of FLNs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this finding, FLNa and FLNb suppress matrix degradation and invasion in HT1080 fibrosarcoma cells. 21 Conversely, in macrophages, FLNa stabilizes podosomes, thus enhancing matrix degradation, 19 indicating that the effect of FLNs on podosome formation and matrix degradation is cell type specific. Altogether, our data support the idea that, in immature DCs, ASB2a acts as a positive regulator of ECM invasion through degradation of FLNs.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, FLN concentration is a crucial determinant in the stiffness of the actin filament network, 11,12 in cell spreading, [13][14][15] in cell adhesion, 15,16 in cell migration, [17][18][19] and in invasion of cancer cells. 20,21 In this context, deciphering the mechanisms controlling levels of FLN may have broad implications for our understanding of FLN functions in normal cells and dysfunctions in pathological contexts. FLN stability is regulated by proteolysis through cleavages by calpains 22 and ubiquitin-mediated proteasomal degradation controlled by the ASB2 E3 ubiquitin ligases.…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al reported that filamin-A regulates focal adhesion disassembly, and that down-regulation of filamin-A enhances the cleavage of focal adhesion proteins [106]. Furthermore, filamin-A has been shown to play a role in ECM degradation and it has been demonstrated that knockdown of filamin-A increases the expression of matrix metalloproteinase-9 (MMP-9) [107] which induces MMP2 activation [108]. …”
Section: Introductionmentioning
confidence: 99%
“…Baldassarre et al showed that knockdown of filamin-A in fibrosarcoma increased matrix metalloprotease 2 activity and activation, enhanced the ability of cells to remodel the ECM, and increased cellular invasive potential without significantly altering two-dimensional random cell migration [108]. In addition, using breast cancer cells that over-express ErbB2, Xu et al reported that knockdown of filamin-A promoted cleavage of focal adhesion in cancer cells and stimulated cancer cell migration, invasion, and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…In many types of connective tissue cells, b1integrinenriched adhesions provide focal sites for ECM remodeling by matrix metalloproteinases (MMPs), a process that is thought to be partly dependent on FLNa (31). Collagen fibrils are also remodeled by phagocytosis (32), an intracellular digestion route for collagen fibrils that involves pericellular fibril fragmentation, internalization, and intracellular digestion by lysosomal cysteine proteinases, such as cathepsins (33, 34).…”
mentioning
confidence: 99%